PENGARUH VOLUME EMISI KARBON, PENGUNGKAPAN EMISI KARBON, DAN TATA KELOLA PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Fujianti, Anisa; Nasihin, Ihsan; Sujaya, Fista Apriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study was driven by the lack of corporate understanding of environmental issues, particularly the magnitude of carbon emissions and the transparency of their disclosure. This lack of understanding can ultimately reduce corporate value. Additionally, the existence of an audit committee and the percentage of independent commissioners are two corporate governance indicators that influence corporate value. Thus, this study aims to examine how corporate governance, carbon emission volume, and disclosure of carbon emissions can influence company value. This study implements a quantitative methodology by applying secondary data from the annual and sustainability reports of coal and energy companies listed on the Indonesia Stock Exchange (IDX). Purposive sampling was used to select the sample, and 12 companies met the established criteria. SmartPLS4 software was used to process the data. Based on the study's findings, corporate governance and carbon emission volume significantly influence company value in the coal industry. However, carbon emissions disclosure does not significantly influence company value in the coal and energy sectors.